2019
DOI: 10.1105/tpc.19.00661
|View full text |Cite
|
Sign up to set email alerts
|

Nup96 and HOS1 Are Mutually Stabilized and Gate CONSTANS Protein Level, Conferring Long-Day Photoperiodic Flowering Regulation in Arabidopsis

Abstract: The nuclear pore complex profoundly affects the timing of flowering; however, the underlying mechanisms are poorly understood. Here, we report that Nucleoporin96 (Nup96) acts as a negative regulator of long-day photoperiodic flowering in Arabidopsis (Arabidopsis thaliana). Through multiple approaches, we identified the E3 ubiquitin ligase HIGH EXPRESSION OF OSMOTICALLY RESPONSIVE GENE1 (HOS1) and demonstrated its interaction in vivo with Nup96. Nup96 and HOS1 mainly localize and interact on the nuclear membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 66 publications
1
49
0
Order By: Relevance
“…A large overlap between DEGs of nup96 and hos1 mutants were observed at 28°C (Figure a–c, Figure S4), indicating a similar role in transcriptome reprogramming at high temperature. This is consistent with the recent finding that NUP96 and HOS1 proteins are mutually stabilized, and they regulate similar biological pathways in some cases (Cheng et al, ). It is yet to be determined if other nup mutants with a high temperature defect also have this transcriptome pattern.…”
Section: Discussionsupporting
confidence: 92%
“…A large overlap between DEGs of nup96 and hos1 mutants were observed at 28°C (Figure a–c, Figure S4), indicating a similar role in transcriptome reprogramming at high temperature. This is consistent with the recent finding that NUP96 and HOS1 proteins are mutually stabilized, and they regulate similar biological pathways in some cases (Cheng et al, ). It is yet to be determined if other nup mutants with a high temperature defect also have this transcriptome pattern.…”
Section: Discussionsupporting
confidence: 92%
“…Photoreceptors Phytochrome B (PHYB) and Zeitlupe (ZTL) destabilize CO in the morning while Phytochrome A (PHYA), Cryptochromes (CRYs) and Flavin-Binding, Kelch Repeat F-box1 (FKF1) stabilize CO in the afternoon under LD 10 13 . The interaction between Nucleoporin 96 (Nup 96) and HOS1 and their mutual stabilization form a novel repressive module to gate CO protein level in Arabidopsis under LD 14 . GIGANTEA (GI) plays a pivotal regulation on the timing stabilization of CO by altering FKF1-ZTL interaction 15 .…”
Section: Introductionmentioning
confidence: 99%
“…6). Previous studies have confirmed that some Nups (AtNup54, AtNup62, AtNup96, AtNup160, and AtHOS1) affect flowering time in Arabidopsis thaliana 1,[23][24][25] . And the tissue-specificity analysis found that MdNup54, MdNup62, MdNup133, and MdNup160 were most highly expressed in buds, and MdNup93 was also highly expressed in buds, suggesting that these genes may be involved in the apple flowering pathway.…”
Section: Evolutionary Relationship Between Mdnup54 and Mdnup62 Among mentioning
confidence: 76%
“…However, Tissue specific expression only provides reference for the potential function of Nups, which need to be experimentally verified. Arabidopsis thaliana studies have confirmed that some Nups (AtNup54, AtNup62, AtNup96, AtNup160, and AtHOS1) affect flowering time 1,[23][24][25] . However, little is known about their potential roles in apple-induced flowering.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation